Estimates of the excess cost burden of Ehlers-Danlos syndromes: a United States MarketScan® claims database analysis - Schubart, Jane R.; Schaefer, Eric W.; Knight, Dacre R. T.; Mills, Susan E.; Francomano, Clair A. (Frontiers in Public Health, 2024)
Patients with Ehlers-Danlos syndromes (EDS) and hypermobility spectrum disorders (HSD) have significant health challenges that are well-documented, however their impact in terms of cost is not known. Our research objective was to examine the cost burden of EDS and HSD in the United States. We focused this analysis on those with commercial insurance plans.We queried the MarketScan® database for year 2021 for claims that contained an ICD-10 diagnosis code for EDS or hypermobility. Excess costs for patients in the EDS and HSD cohorts were determined by matching each patient to one patient in the database that did not have a claim for EDS or HSD and comparing total costs for the calendar year. We determined whether patients had claims for selected comorbid conditions likely to impact costs during the calendar year.Results: Sample sizes were 5,113 for adult (age ≥18) patients with EDS, 4,880 for adult patients with HSD, 1,059 for child (age 5-17) patients with EDS, and 2,427 for child patients with HSD. The mean excess costs were 21,100 for adult EDS patients, 11,600 for adult HSD patients, 17,000 for child EDS patients, and 11,000 for child HSD patients. EDS and HSD cohorts, both adults and children, with any of the comorbidities had greater healthcare costs. The largest difference was found in the EDS cohort with gastrointestinal comorbid conditions, with more than double the costs for adults.Discussion: We found that patients in the Marketscan database, adults and children, who had EDS or HSD had substantially higher associated excess healthcare costs than patients without EDS or HSD when considering age, sex, geographic location, and comorbidities. These disproportionate healthcare